Explicating anti-amyloidogenic role of curcumin and piperine via amyloid beta (Aβ) explicit pathway: recovery and reversal paradigm effects - Abdul Manap, Aimi Syamima; Madhavan, Priya; Vijayabalan, Shantini; Chia, Adeline; Fukui, Koji (PeerJ, 2020)
Previously, we reported the synergistic effects of curcumin and piperine in cell cultures as potential anti-cholinesterase and anti-amyloidogenic agents. Due to limited findings on the enrolment of these compounds on epigenetic events in AD, we aimed at elucidating the expression profiles of Aβ42-induced SH-SY5Y cells using microarray profiling. In this study, an optimized concentration of 35 µM of curcumin and piperine in combination was used to treat Aβ42 fibril and high-throughput microarray profiling was performed on the extracted RNA. This was then compared to curcumin and piperine used singularly at 49.11 µM and 25 µM, respectively. Our results demonstrated that in the curcumin treated group, from the top 10 upregulated and top 10 downregulated significantly differentially expressed genes (p < 0.05; fold change ≥ 2 or ≤ −2), there were five upregulated and three downregulated genes involved in the amyloidogenic pathway. While from top 10 upregulated and top 10 downregulated significantly differentially expressed genes (p < 0.05; fold change ≥ 2 or ≤ − 2) in the piperine treated group, there were four upregulated and three downregulated genes involved in the same pathway, whereas there were five upregulated and two downregulated genes involved (p < 0.05; fold change ≥ 2 or ≤ − 2) in the curcumin-piperine combined group. Four genes namely GABARAPL1, CTSB, RAB5 and AK5 were expressed significantly in all groups. Other genes such as ITPR1, GSK3B, PPP3CC, ERN1, APH1A, CYCS and CALM2 were novel putative genes that are involved in the pathogenesis of AD. We revealed that curcumin and piperine have displayed their actions against Aβ via the modulation of various mechanistic pathways. Alterations in expression profiles of genes in the neuronal cell model may explain Aβ pathology post-treatment and provide new insights for remedial approaches of a combined treatment using curcumin and piperine.
Keywords: Anti-amyloidogenic; Curcumin; Piperine; Microarray; Aβ42 fibril